1946
DOI: 10.1037/h0063378
|View full text |Cite
|
Sign up to set email alerts
|

The study of eye movements in reading.

Abstract: The present review covers material appearing in the literature from 1935 to 1944. The studies are reviewed under the following headings: techniques of measurement, analysis of the reading process, oculomotor co-ordination, factors in variability, special reading situations, heredity and certain environmental factors, eye movements in the reading clinic, training eye movements, and central versus peripheral processes. Certain studies on eye movements in viewing pictures and advertisements, studies of visual fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
4

Year Published

1952
1952
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 86 publications
1
36
0
4
Order By: Relevance
“…This research has parallels in the visual reading literature, which has shown a correlation between eye fixation patterns and reading ability (Nodine & Lang, 1971;Nodine & Simmons, 1974;Tillson, 1955). However, the most convincing interpretation of this correlation appears to be that poor eye movement control is a result, not a cause, of poor reading ability (Just & Carpenter, 1980;Stanley, 1978;Tinker, 1946Tinker, , 1958. Such a conclusion is based on evidence from oculomotor training studies that were effective in altering subjects' eye movements but not in .…”
Section: Braille Comprehension Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This research has parallels in the visual reading literature, which has shown a correlation between eye fixation patterns and reading ability (Nodine & Lang, 1971;Nodine & Simmons, 1974;Tillson, 1955). However, the most convincing interpretation of this correlation appears to be that poor eye movement control is a result, not a cause, of poor reading ability (Just & Carpenter, 1980;Stanley, 1978;Tinker, 1946Tinker, , 1958. Such a conclusion is based on evidence from oculomotor training studies that were effective in altering subjects' eye movements but not in .…”
Section: Braille Comprehension Abilitymentioning
confidence: 99%
“…Such a conclusion is based on evidence from oculomotor training studies that were effective in altering subjects' eye movements but not in . improving subjects' comprehension performance (Tinker, 1946(Tinker, , 1958 and from observations that poor readers' immature eye movements do not generalize to nonreading scanning tasks such as picture scanning (Stanley, 1978). A similar conclusion about the relationship between hand movements and braille comprehension may be forthcoming.…”
Section: Braille Comprehension Abilitymentioning
confidence: 99%
“…If eye movements were a causative factor in reading disability, then the problem could easily be diagnosed with a simple eye movement test, and oculomotor training would result in improved reading. Although there have been some demonstrations that oculomotor training improves reading performance (see Solan, 1985), Tinker (1946Tinker ( , 1958 and Rayner (1985b) argued quite strongly that eye movements were generally not a cause of reading disability but were a reflection of other underlying problems.…”
Section: Eye Movements Poor Readers and Dyslexiamentioning
confidence: 99%
“…Les travaux antérieurs (i.e. Tinker, 1946 ;Noton & Stark, 1971 ;Bahill & Stark, 1987 ;Massen, 2002 ;Delorme & Flückinger, 2003), étudiant les facteurs qui influencent la planification et l'exécution de saccades ainsi que les durées de fixations, ont su établir des liens entre le comportement cognitif et les indices oculaires. Le lien entre cognition et fixation est évidemment particulièrement saillant dans les paradigmes de lecture.…”
Section: Approche Psycho-physiologique : Enregistrements Oculairesunclassified